PENGARUH STRATEGI PEMBELAJARAN INKUIRI BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS KARANGAN ARGUMENTASI SISWA KELAS X SMA NEGERI 2 LENGAYANG KABUPATEN PESISIR SELATAN - Hartidini, Suci; R.,, Syahrul; Ratna, Ellya (Universitas Negeri Padang, 2018)
This article of research to describing the comprehension of vocabulary, describing the writing skill of description text, and describing the contribution of vocabulary towards the skill in writing description text at students grade X SMA Negeri 2 Lengayang Kabupaten Pesisir Selatan. The method used is this research is descriptive and correlational design. Based of result data analyze and explanation, were concluded 3 case. First, comprehension of vocabulary students grade at X SMA Negeri 2 Lengayang Kabupaten Pesisir Selatan was on good qualification (77,43). Second, writing skills of description text at students grade X SMA Negeri 2 Lengayang Kabupaten Pesisir Selatan was on good qualification (79,01). Third, comprehension vocabulary contributed toward writing skills description text at students grade X SMA Negeri 2 Lengayang Kabupaten Pesisir Selatan. Kata kunci: strategi pembelajaran, inkuiri, media audivisual, karangan argumentasi